Self-Reflection Journal in Action: A Case in English Syntax Class in Higher Education - Surtikanti, Monika Widyastuti; Nurcahyoko, Kunto; Agung, Antonius Setyawan Sugeng Nur (Indonesian Journal of Educational Research and Review, 2024)
Students' linguistics knowledge, especially on sentence structure, is urgently needed for English Pre-Service teachers as an essential skill. However, English pre-service teachers in a private university in West Kalimantan faced various challenges in learning it. The present study aims to analyze self-reflection journal realization and students' views in English Syntax courses in higher education. This study included 20 English Pre-Service teachers from semester 5 who were enrolled in two classes of the English Syntax course. It utilized a qualitative method and a case study approach. The purposive sampling method was employed to select representative and communicative participants. They wrote self-reflection journals on three topics in the English Syntax syllabus. The result showed that self-reflection journals were useful for the students in evaluating their progress on each topic. Self-reflection journals triggered the students' self-awareness and self-development, which benefited the teaching and learning process. According to the students, they were delighted to evaluate their process and find a new solution for their future learning strategy. Moreover, the present study might provide a new paradigm for the use of self-reflection journals in English Syntax courses other than Writing skills. Future research is recommended to develop the self-reflection journal instrument to gain a more authentic reflection entry.